Pelaksanaan Perlindungan Hak-Hak Pekerja Penyandang Disabilitas Pada Badan Hukum Nirlaba Di Yayasan Bunga Bali - I Dewa Gede Aditya Mahendra Putra; I Nyoman Putu Budiartha; Ni Komang Arini Styawati (Jurnal Konstruksi Hukum, 2022)
People with disabilities sometimes receive less attention or are often discriminated against. The expectations of persons with disabilities in obtaining employment are relatively low, compared to those without physical disabilities. Foundations have an important role in dealing with various problems that are currently occurring and the fulfillment of the rights of workers with disabilities has been obtained through the existence of foundations or non-profit organizations. This research was conducted to examine the implementation of the protection of the rights of workers with disabilities in the Non-Profit Legal Entity at the Bunga Bali Foundation. The method used in this research is an empirical method with a sociological approach. Sources of data used in the form of primary and secondary data. The data analysis method used in this research is a qualitative method. The results of this research reveal that all existing regulations have been implemented by the foundation, but some companies are not ready to have employees with conditions as persons with disabilities, making it difficult for the foundation to channel workers with disabilities to work outside the company and obstacles in fulfilling the rights for people with disabilities. workers with disabilities by a non-profit legal entity at the Bunga Bali foundation and if later there is an obstacle, the foundation will immediately discuss the existing obstacles and as soon as possible the foundation will find a way out.